Talking to God Among a Cloud of Witnesses: Collective Prayer as a Meaningful Performance - Fuist, Todd Nicholas (Journal for the scientific study of religion, 2015)
There has been much work on the effects that individual prayer has on a variety of social-psychological indicators, yet there remains a lack of research on collective prayer. While it is tempting to assume that collective prayer may be analyzed as the aggregate of individual prayers, the research presented in this article suggests that worshipers pray differently when in community than when by themselves. To understand the role of collective prayer in the practices of faith communities, I draw on work on group culture and ritual to create a framework for analyzing collective prayer. I assert that collective prayer represents a meaningful social performance that locates those conducting it within wider fields of meaning. I conclude with suggestions for future work, including examining how collective prayer acts as an element of conflict as well as unity.